Enhancing Diagnostic Precision in Non‐Immune Hydrops Fetalis: The Incremental Value of Whole Exome Sequencing—A Prospective Cohort Study - Charu Sharma; Meenakshi Gothwal; Dolat Singh Shekhawat; Taruna Yadav; Manisha Jhirwal; Nayan Tada; Kratika Badi; Shashank Shekhar; Pratibha Singh; Kuldeep Singh (Clinical Genetics, 2026)
ABSTRACT Non‐immune hydrops fetalis (NIHF) is a phenotypically heterogeneous condition associated with substantial perinatal morbidity and mortality and its underlying etiology often remains unresolved despite comprehensive conventional investigations. We evaluated the etiological spectrum of NIHF and the additional diagnostic contribution of whole‐exome sequencing (WES) in a prospective cohort from Western Rajasthan, India. Eighty consecutive fetuses with NIHF were enrolled between January 2020 and March 2026. Fetuses with immune hydrops or twin‐to‐twin transfusion syndrome were excluded. All cases underwent detailed fetal ultrasonography, fetal echocardiography, targeted infectious screening and conventional genetic evaluation, including karyotyping with or without chromosomal microarray. WES was performed in unresolved cases and variants were interpreted according to ACMG/AMP guidelines. The proportion of NIHF in the study population was 0.42% and an underlying diagnosis was established in 40 of 80 cases (50.0%). Genetic disorders accounted for 27 of 40 diagnosed cases (67.5%), including aneuploidies in 12 cases (15.0% of the overall cohort) and pathogenic monogenic disorders in 15 cases (18.8%). Non‐genetic etiologies included structural anomalies, parvovirus B19 infection and lower urinary tract obstruction. WES was performed in 41 fetuses and identified pathogenic or likely pathogenic variants in 15 cases, corresponding to a diagnostic yield of 36.6%, while variants of uncertain significance were identified in six cases (14.6%). The overall incremental diagnostic yield of WES was 18.8% (15/80). Consanguinity was significantly associated with a higher WES diagnostic yield compared with non‐consanguineous families (69.2% vs. 21.4%; odds ratio 8.25, p = 0.005). WES substantially improved diagnostic resolution in fetuses with NIHF, identifying an underlying monogenic disorder in more than one‐third of tested cases. Incorporation of genomic sequencing into the diagnostic evaluation of unresolved NIHF, particularly in consanguineous families, recurrent cases or fetuses with syndromic features, may improve prognostication, facilitate recurrence‐risk assessment and inform reproductive counselling.